O-GlcNAc transferase and O-GlcNAcase: achieving target substrate specificity - Nagel, Alexis K. (Amino Acids, 2014)
O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA) catalyze the dynamic cycling of intracellular, post-translational O-GlcNAc modification on thousands of Ser/Thr residues of cytosolic, nuclear, and mitochondrial signaling proteins. The identification of O-GlcNAc modified substrates has revealed a functionally diverse set of proteins, and the extent of O-GlcNAcylation fluctuates in response to nutrients and cellular stress. As a result, OGT and OGA are implicated in widespread, nutrient-responsive regulation of numerous signaling pathways and transcriptional programs. These enzymes are required for normal embryonic development and are dysregulated in metabolic and age-related disease states. While a recent surge of interest in the field has contributed to understanding the functional impacts of protein O-GlcNAcylation, little is known about the upstream mechanisms which modulate OGT and OGA substrate targeting. This review focuses on elements of enzyme structure among splice variants, post-translational modification, localization, and regulatory protein interactions which drive the specificity of OGT and OGA toward different subsets of the cellular proteome. Ongoing efforts in this rapidly advancing field are aimed at revealing mechanisms of OGT and OGA regulation to harness the potential therapeutic benefit of manipulating these enzymes’ activities.